2001
DOI: 10.1021/ic0006089
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Rearrangements in Six-Coordinate Ruthenium and Iron Dihydrides

Abstract: Molecular orbital calculations at the ab initio level are used to study polytopal rearrangements in H2Ru(PH3)4 and H2Fe(CO)4 as models of 18-electron, octahedral metal dihydrides. It is found that, in both cases, the transition state for these rearrangements is a dihydrogen species. For H2Fe(CO)4, this is a square pyramidal complex where the H2 ligand occupies an apical position and is rotated by 45 degrees from its original orientation. This is precisely analogous to the transition state for Fe-olefin rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…The proposed isomerization mechanism involved hydride migration from one tetrahedron (formed by FeL 4 ) face to another by traversing the edge connecting the two faces. Computational studies of H 2 Fe(CO) 4 , however, suggested that the intramolecular rearrangement proceeded via a 5‐coordinate Fe(0) dihydrogen complex . Complex H 3 Fe(PEtPh 2 ) 3 (SnPh 3 ) was shown to contain a tetrahedral FeP 3 Sn core with three hydride ligands bridging iron and tin (Figure ) .…”
Section: Monodentate Ligand Systemsmentioning
confidence: 99%
“…The proposed isomerization mechanism involved hydride migration from one tetrahedron (formed by FeL 4 ) face to another by traversing the edge connecting the two faces. Computational studies of H 2 Fe(CO) 4 , however, suggested that the intramolecular rearrangement proceeded via a 5‐coordinate Fe(0) dihydrogen complex . Complex H 3 Fe(PEtPh 2 ) 3 (SnPh 3 ) was shown to contain a tetrahedral FeP 3 Sn core with three hydride ligands bridging iron and tin (Figure ) .…”
Section: Monodentate Ligand Systemsmentioning
confidence: 99%
“…321 Nevertheless, some six-coordinate dihydrides of iron and ruthenium show stereochemically nonrigid behavior. 322 For example, a low-temperature limiting spectrum is observed at −50…”
Section: Six-coordination and Nonrigiditymentioning
confidence: 99%
“…Hydride -dihydrogen equilbria which allows conversion to five-coordination could also rationalize the low barriers for some octahedral dihydrides. 322 SST experiments have also indicated a dihydride intermediate in rearrangements of pseudooctahedral Re(CO)(NO)L 2 (H 2 ).…”
Section: Six-coordination and Nonrigiditymentioning
confidence: 99%
“…321 Nevertheless, some six-coordinate dihydrides of iron and ruthenium show stereochemically nonrigid behavior. 322 For example, a low-temperature limiting spectrum is observed at −50 • C for Fe[PPh(OEt) 2 ] 4 H 2 and shows both cis and trans isomers. Hydride -dihydrogen equilbria which allows conversion to five-coordination could also rationalize the low barriers for some octahedral dihydrides.…”
Section: Six-coordination and Nonrigiditymentioning
confidence: 99%
“…Hydride -dihydrogen equilbria which allows conversion to five-coordination could also rationalize the low barriers for some octahedral dihydrides. 322 SST experiments have also indicated a dihydride intermediate in rearrangements of pseudooctahedral Re(CO)(NO)L 2 (H 2 ). 323 Fluxionality has also been observed in chelated octahedral complexes.…”
Section: Six-coordination and Nonrigiditymentioning
confidence: 99%